Synergistic mastery: Advancing mechanical and electrical harmony in conducting polymer hydrogel bioelectronics - Ting Wang; Jiajun Liu; Yuli Zhao; Yuan Lu (Bioactive Materials)
Conducting polymer hydrogels offer promising electrical interfaces with biological tissues for electrophysiological signal recording, sensing, and stimulation due to their favorable electrical properties, biocompatibility, and stability. Among them, Poly (3,4-ethylenedioxythiophene): Polystyrene sulfonate (PEDOT:PSS) is widely used as a conductive filler, forming a network of conjugated nanofibers within the hydrogel matrix. This structure enables robust electronic conductivity while preserving ionic transport and biocompatibility in physiological environments. However, the mechanical integrity of these hydrogels is often compromised by micellar microstructures in aqueous colloidal dispersions. The absence of interconnected conducting polymer nanofibers to maintain mechanical integrity during swelling hinders the mechanical properties of hydrogels. Here, three modification strategies were explored to enhance the flexibility and stretchability: constructing an interpenetrating network, phase separation induced by ionic compounds, and pure conductive hydrogels formed through polar solvent additives and dry-annealing. These strategies synergistically enhance conductivity and flexibility by controlling interchain entanglement and redesigning the distribution of conjugated crystal regions and soft regions. The resulting hydrogels exhibit excellent conductivity (1.99–5.25 S/m), softness (elastic modulus as low as 280 Pa), and elasticity (tensile properties up to 800 %). When used as epidermal or implantable bioelectrodes, they provided a soft interface, ensuring longer-lasting and more stable electromyogram, electrocardiogram, and electroencephalogram signals compared to commercial gel electrodes, with a signal-to-noise ratio of up to 20.0 dB. Therefore, the conducting polymer hydrogels developed in this study leverage the synergy between conductivity and flexibility, paving the way for further transformative applications in bioelectronics.